PENGARUH RASIO PROFITABILITAS, RASIO LEVERAGE, RASIO LIKUIDITAS TERHADAP PERINGKAT SUKUK - Novi Maulani Syamsudin; Widya Febryari Anita (Jurnal Widya Akuntansi dan Keuangan, 2022)
This study aims to provide empirical evidence about the factors that influence the ratings of Islamic commercial banks in Indonesia. This study examines the role of financial ratios which include: profitability ratios, leverage ratios, and liquidity ratios. The research method used is purposive sampling, with the following criteria: 1) Corporate companies that issue sukuk and are registered at ISSI and ranked at PT. PEFINDO, 2) a corporate company that issues sukuk and is registered with ISSI and rated at PT. PEFINDO which went public after 2015, and 3) companies that publish quarterly reports on the company's official website for 2016-2020. The data analysis technique used is multiple linear regression. The results of this study indicate that simultaneously profitability, leverage and liquidity variables have a significant effect on the sukuk rating of corporate companies that issue sukuk and are listed on ISSI and rated at PT. PEFINDO. Partially, profitability and liquidity have a significant effect on the sukuk rating. Partially, leverage has no significant effect on the sukuk rating.